Policespeak: Metode Interogasi dalam Serial Bertema Investigasi Kejahatan - Umam, Robith Khoiril (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
Investigation to reveal crime cases needs collaboration from many sources. After the evidences and witnesses are identified, the next process is inviting the suspects to an investigation stage to collect important information in an interrogation. Addressing the research gap left by the previous studies that explored this aspect too specific or too broad, this research aims at describing the interrogation methods used by the police during interrogating the suspect in crime investigation themed series and describing what factors influencing the selection of those methods by using taxonomy of interrogation proposed by Kelly et al (2013). The research employs Spradley (2016) theory in analysing the data, consisting of domain, taxonomy, componential analysis and finding cultural theme. The result of the research shows that the interrogation methods applied are categorized into two poles. Firstly, minimalization or an attempt reduce the seriousness of the offense to the suspect that based on friendliness and cooperative principle like collaboration, and rapport and relationship building. Secondly, maximalization or an attempt to emphasize the seriousness of the offense or intimidating the suspect like confrontation and competition, presentation of evidence, context manipulation and emotion provocation. The factors influencing the selection of the methods are the gender and age of the suspect and interrogator, public and government attention toward the crime case, and the characteristics of the suspects, whether he is resistant or cooperative.